Penyelesaian Wanprestasi dalam Perjanjian Simpan Pinjam pada Koperasi Syariah Benteng Mikro IndonesiaDitinjau dari Undang-Undang Nomor 25 Tahun 1992 tentang Perkoperasian - Deriel Venus Kurniawan; Khaerul (CV. Kurnia Grup, 2026)
This study discusses the settlement of defaults in savings and loan agreements at the Benteng Micro Indonesia Sharia Cooperative (BMI). The problem of default in cooperatives is an important problem because it can affect the financial stability of the cooperative, the legal relationship between the cooperative and members, and the level of trust of members in the cooperative. This study aims to analyze the legal provisions regarding savings and loan agreements in sharia cooperatives and examine the default settlement mechanism applied to BMI Sharia Cooperatives. The research method used is normative legal research with a legislative approach, a conceptual approach, and a case approach. The legal materials used consist of primary, secondary, and tertiary legal materials obtained through literature studies. Furthermore, legal materials are analyzed in a qualitative descriptive manner to obtain a systematic understanding of the research problem. The results of the study show that savings and loan agreements in sharia cooperatives are basically subject to the provisions of the Civil Code and regulations in the field of cooperatives, and are influenced by sharia principles that emphasize justice and balance. The form of default that occurs is generally in the form of late payment, non-fulfillment of payment obligations, or the implementation of obligations that are not in accordance with the content of the agreement. Settlement of defaults in BMI Sharia Cooperatives prioritizes the non-litigation route through deliberation, negotiation, mediation, and collection consistently by prioritizing the principle of kinship. However, there are still several obstacles, such as weak dispute resolution documentation, lack of strict implementation of sanctions, and low legal understanding of cooperative members and management. Based on the results of the research, it is necessary to strengthen the legal aspect in resolving defaults without overriding family values that are characteristic of cooperatives. Thus, the settlement of defaults is expected to be able to provide legal certainty, protection for the parties, and maintain the sustainability of cooperatives as community-based economic institutions.